2019
DOI: 10.1111/1365-2745.13164
|View full text |Cite
|
Sign up to set email alerts
|

Spartina alterniflora invasion drastically increases methane production potential by shifting methanogenesis from hydrogenotrophic to methylotrophic pathway in a coastal marsh

Abstract: Plant invasion can strongly influence carbon (C) cycling processes, thus it may affect climate change by altering C sequestration and greenhouse gas emissions in the invaded ecosystem. Since 1979, the exotic Spartina alterniflora has rapidly expanded in China’s coastal areas, where significant increase in methane (CH4) emissions has been documented from post‐invaded sites. However, a mechanistic understanding of the structural and functional changes of associated methanogens accompanying this invasion remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 88 publications
(117 reference statements)
0
16
0
Order By: Relevance
“… S. alterniflora invasion in coastal wetlands of China strongly influenced the soil microbial communities and their associated functions ( 38 , 39 ). S. alterniflora can supply specific soil microorganisms with certain substrates, such as trimethylamine ( 63 , 64 ). Here, we suggested that the changes of aboveground plant species were more closely associated with RT than with AT ( Table S1B ), due to RT’s narrower niche breadth and ecological preferences for certain habitats and resources ( 11 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… S. alterniflora invasion in coastal wetlands of China strongly influenced the soil microbial communities and their associated functions ( 38 , 39 ). S. alterniflora can supply specific soil microorganisms with certain substrates, such as trimethylamine ( 63 , 64 ). Here, we suggested that the changes of aboveground plant species were more closely associated with RT than with AT ( Table S1B ), due to RT’s narrower niche breadth and ecological preferences for certain habitats and resources ( 11 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…alterniflora invasion in coastal wetlands of China strongly influenced the soil microbial communities and their associated functions (38,39). S. alterniflora can supply specific soil microorganisms with certain substrates, such as trimethylamine (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting effects of the two species on CH 4 emissions may also be caused by differences in electron donor input, such as higher rates of root exudation in Spartina vs. Schoenoplectus rhizospheres. Recent studies in Chinese tidal wetlands demonstrated that invasive Spartina alterniflora stimulated CH 4 emissions through higher exudation of labile organic substrates from S. alterniflora roots in comparison to native species 15,51 . We do not have data on root exudate quality and quantity in Spartina-vs. Schoenoplectus-dominated mesocosms, but data from the adjacent reference marsh platform indeed show markedly higher porewater concentrations of dissolved organic C in Spartina 41,52 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, direct electron transfer by conductive pili/protein and indirect electron transfer by H 2 /formate work together for CO 2 reduction to generate biomethane. Third, methylotrophic methanogenesis reduces the methyl group of, e.g., methanol and methylamine, to methane ( Yuan et al, 2019 ; Conrad, 2020 ); this process contributes only a small amount of methane production in bioengineering. Mustapha et al (2016) showed the simultaneous functions and interactions of diverse bacteria and methanogenic archaea at different stages of the anaerobic digestion of waste-activated sludge.…”
Section: Effects Of Antibiotics On Anaerobic Digestionmentioning
confidence: 99%